2019
DOI: 10.3390/ma12101679
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photocatalytic Activity under Visible Light Irradiation via the AgI@TCNQ Core-Shell Structure

Abstract: In this paper, a AgI@TCNQ photocatalyst with a core-shell structure was reported. A two-dimensional TCNQ (7,7,8,8-Tetracyanoquinodimethane) nanosheet, with a π-π conjugate structure, was used as a shell layer to realize the flexible coating on the surface of AgI nanoparticles. These special core-shell structure composites solve the key problems of the small interface of the bulk composites and the lesser charge transfer paths, which could accelerate the migration of photogenerated carriers. Thus, the AgI@TCNQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Xie’s group [ 31 ] successfully synthesized AgI @ TCNQ composites for the photocatalytic degradation of methylene blue (MB) and found that the degradation rate of the composites was 1.8 times higher than that of AgI.…”
Section: Introductionmentioning
confidence: 99%
“…Xie’s group [ 31 ] successfully synthesized AgI @ TCNQ composites for the photocatalytic degradation of methylene blue (MB) and found that the degradation rate of the composites was 1.8 times higher than that of AgI.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained XRD pattern of the WO3 indica t ed that characteristic diffraction peaks of monoclinic WO3 observed at 23.1 (002); 23.7 (020): 24.4 (200) and 34,1° (202) (JCPDS: 43-1035) [12-14]. The XRD diffractogram of the synthesized AgI displayed three overt diffractio n peaks at 23.6; 39.1 and 46.4 o , which respectively pertained to (002), (110) and (112) planes of the typical hexagonal AgI[15][16][17]. For WO3/AgI composites, the XRD diffractogram of the synthesized samples exhibited wide triplet diffraction peaks at 2θ in range of 22.5 to 25.…”
mentioning
confidence: 99%